Assessing the Economic Value of Pharmacy Resident Participation in an Investigational Drug Service. (February 2021) - Brown, Jamie N.; Gordon, Sara E.; Tillman, Frank; Jacob, Sherin; Britnell, Sara R.
Purpose: Completion of postgraduate residency training gives pharmacists an opportunity to gain advanced practice experience, yet the availability of these positions is often limited. Through participation in an investigational drug service (IDS), residency programs may be able to expand learning experiences while demonstrating a financial benefit to the institution. The purpose of this assessment is to examine the economic value generated by pharmacy resident involvement within an IDS. Methods: This was a single-center retrospective record review. All resident dispensations within the IDS from January 1, 2016, to December 31, 2017, were evaluated for cost avoidance, revenue, and waived revenue. Cost avoidance was defined as the cost of medications the institution would have incurred had the sponsor not provided therapies free of charge. Medical center contract acquisition costs were used to determine cost avoidance. Total economic value accounted for the personnel costs of resident dispensations. Descriptive statistics were utilized for all assessments. Results: A total of 444 resident dispensations occurred during the study period on 15 IDS protocols. The total cost avoidance for resident dispensations was US144 898. Total revenue for these dispensations was US1424, and waived revenue fees totaled US17 625. After accounting for the personnel cost of dispensations by the residents, the total economic value of resident participation in the IDS was US159 150. Conclusion: Resident participation in the IDS contributed economic value to the institution. The IDS provides a unique learning experience for the pharmacy residents, cost savings for the institution, and supports the advancement of patient care.